MANAGEMENT OF TOOTH EXTRACTION WITH LOCAL ANESTHESIA IN ELDERLY WITH DIABETES MELLITUS AND OBESITY: LITERATURE REVIEW - Fatkhurrohman, Fuad; Matta Nydia, Fidela; Rahmawati, Rizqika (Journal of Health and Dental Sciences, 2025)
Dental health in the elderly is significantly influenced by aging and systemic conditions such as diabetes mellitus and obesity, which increase the risk of complications during dental procedures, particularly tooth extraction. . Diabetes can impair wound healing and heighten susceptibility to infection, while obesity is associated with increased procedural risks. Proper management of local anesthesia and a comprehensive medical approach are key to the success of tooth extraction procedures in elderly patients with diabetes mellitus and obesity. This literature review aims to analyze the role of local anesthesia in the management of tooth extraction in elderly patients with diabetes mellitus and obesity.This study uses a literature review method to evaluate and synthesize research on local anesthesia in dental procedures for patients with hypertension, diabetes, and obesity in older people. Articles used were sourced from databases such as Google Scholar, PubMed, Science Direct, and ResearchGate, covering publications from 2000 to 2023. The selected literature focuses on the effects of local anesthesia on related medical conditions and its implications in dental practice for elderly patients. Tooth extraction management in elderly patients with diabetes mellitus and obesity requires a cautious approach, including blood sugar control, appropriate local anesthesia selection, and careful monitoring of vital signs to prevent complications. Effective communication between the dentist and the patient is crucial to reduce anxiety, while intensive post-operative care and pain management are also critical in the recovery process. With the right approach, the extraction procedure can be performed with minimal complications in elderly patients with these medical conditions. DOI : 10.54052/jhds.v5n1.p1-18